PREVALENCE OF ESCHERICHIA COLI, COLIFORM AND NON-COLIFORM BACTERIA IN MUD BUFFALO IN RANGGAGATA AND SERAGE VILLAGES, SOUTHWEST PRAYA SUBDISTRICT, DISTRICT OF CENTRAL LOMBOK, WEST NUSA TENGGARA - Erwin Satriawan; I Nengah Kerta Besung; I Gusti Ketut Suarjana (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Escherichia coli (E. coli) is a common bacterium that inhabits the intestines of humans and animals with hundreds of different strains, both harmful and harmless. One of the diseases that can be caused by E. coli is diarrhea. Diarrhea is a disease in the form of increased frequency of defecation, thinner stool consistency and increased intestinal peristalsis. This study aims to determine the number of E. coli, coliform and non-coliform bacteria in mud buffaloes in Ranggagata and Serage Villages, Southwest Praya Subdistrict, Central Lombok Regency, West Nusa Tenggara with samples used are fresh feces samples, a total of 14 samples. Sample cultivation was carried out on Eosin methyleneblue agar (EMBA) media then samples suspected of E. coli colonies were Gram stained, and biochemical tests on Triple Sugar Iron Agar (TSIA) media, Sulfide Indole Motility (SIM), Methyl red-Voges Proskauer (MR-VP) media, Simmons Citrate and catalase tests. The results showed the number of bacterial populations varied depending on the age of the buffalo with an average number of E. coli bacteria 162.143 ± 196.476, average coliform 272.000± 328.307 and average non-coliform 110.714 ± 201.855. Based on the results of the study it can be concluded that there is an increase in the number of E. coli, coliform and non-coliform as the age of buffalo increases, namely for E. coli is Y = 2.527+0.009x, coliform is Y = 2.525+0.05x and non-coliform bacteria is Y = 3.199+0.007x. Further tests need to be conducted related to other strains or species of E. coli, coliform and non-coliform bacteria in mud buffalo feces.